Eksplorasi Etnomatematika dalam Makanan Tradisional Kerupuk Enye Khas Jampang Tengah Sukabumi: Analisis Konsep Rasio dan Proporsi - Nuryatul Salwa Qolbiyah; Nurul Arfinanti; Santi Widyawati; Elvin Ervi Ladona (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2025)
Ethnomathematics is a field of study that examines the relationship between local cultural practices and mathematical concepts, offering a meaningful bridge between formal mathematics and the sociocultural realities of communities. This study aims to explore ethnomathematical aspects embedded in kerupuk Enye, a traditional food from Central Jampang, as an effort to preserve local culture while promoting innovation in contextual mathematics learning. Employing a qualitative ethnographic approach, the study investigates mathematical elements present in the production process of kerupuk Enye. Data was collected through in-depth virtual interviews with a local practitioner with over ten years of experience, complemented by indirect observation of the production stages documented by family members. The findings reveal that the production process involves mathematical concepts related to ratios and proportions, particularly in ingredient measurement and scaling. These results indicate that kerupuk Enye production practices can serve as a highly contextual and culturally relevant learning resource for teaching ratios and proportions at the Grade VII level. This study contributes to the integration of local cultural knowledge into mathematics education, supporting culturally responsive and meaningful learning experiences